Alkoholizm, prostytucja, zakażenia HIV i AIDS, narkomania jako formy wykluczenia społecznego (w świetle badań) - Korporowicz, Violetta (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2012)
The growth of social exclusion may be affected many aspects of social life such as alcoholism, prostitution and drug addiction. Particularly worrying is the growth of alcoholism among young people in Poland. A 2009 study conducted in Poland by WHO states that 11–15-year-old students in Poland are attempting to drink alcohol. Prostitution is another social phenomenon affecting the development of social exclusion. The most common cause of prostitution in Poland is difficult financial situation and inability to obtain work. Another negative phenomenon, which may affect the growth of social exclusion is drug addiction. The reasons for importance of drug abuse among social problems are not only quantitative parameters, but also the dynamics of the phenomena and changes in the structure of the population affected by the problem. Synthetic studies of the spread of drug addiction emphasize that the increasing rate of the phenomenon goes beyond its reach and environmental groups traditionally associated with drug addiction. This is the reason why it is so hard to help the drug addicts.